The playeur and Pokémon Go: Examining the effects of locative play on spatiality and sociability. (May 2019) - Evans, Leighton; Saker, Michael
Pokémon Go is a hugely popular hybrid reality game (HRG) that enables players to occupy a space that is simultaneously physical and digital. The general aim of Pokémon Go is to discover and then capture Pokémon. This article reports on an original research project designed to explore the impact of Pokémon Go on spatiality and sociability. The project was conducted between May 2017 and July 2017, using an online survey which received 375 responses from users of Pokémon Go geographically spread across the globe. Drawing on the concept of the "playeur" as an established approach to understanding the effects of locative play on spatiality and sociability, this research follows three lines of enquiry. First, the research examines whether the intermingling of play and ordinary life might encourage players to spend more time outside in public spaces, and how this mode of play is experienced. Second, the research explores whether the game mechanics of Pokémon Go might lead players to traverse their environment using modified routes, as well as to frequent new places. Third, the research examines whether the praxis of Pokémon Go might enable new forms of sociability to emerge that extend beyond earlier HRGs.